Thermal diffusivity measurements using open photoacoustic cell technique - W. Mahmood Mat Yunus; C. Y. J. Fanny,; I. V. Grozescu,; S. A. Halim and,; M. M. Moksin (ASEAN Journal on Science and Technology for Development, 2001)
The application of open photoacoustic cell (OPC) technique is demonstrated for measuring thermal diffusivity of solid samples. It is based upon the measurement of the photoacoustic signal in the modulation frequency region where the thermal diffusion length equals to the sample thickness. The measurements were carried out at room temperature for gold alloys (Au0 75Ag0.and Au. Ag. ); epoxidised natural rubbers 25 0 50 0 50 [ENR  25  (75%C )  and  ENR  50  (75%C)];  and  supercond ucti ng  ceramics (Bi2Pb0 .6 Sr2Ca1.94Ba 0. Cu 0 ,  and Bi Pb . Sr Ca1. Zn. Cu 0 ) . The thermal 06          3       8 2         0 6       2 93         0 07          3       8 diffusivity values obtained in this measurement were in the range of 0.97 for Al down to 1.61 x 10-3 cm2/s for polymer sample.